Optimalizace procesu tažení drátu - Kabilka, David (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Práce řeší studii, rozbor a zhodnocení současného stavu a návrh úpravy technologie nebo parametrů zavádění drátu do tažného zařízení. Problém spočívá v zavádění drátu o průměru 14 mm z materiálu CK 67 do tažné stolice Schumag. Při zavádění drátu do tažné stolice se dvěma průvlaky dochází ke vzpěru drátu a napěchování mezi průvlakem a zaváděcím zařízením. Pro zavádění drátu jsou používány hydraulické zavádějící kleštiny, které jsou ovládány poloautomaticky. Na základě literární studie, výpočtu, simulace a praktického experimentu byly zjištěny podmínky, za kterých je možné stávající metodu zavádění drátu používat.

The aim of work is to present and analyse assessment of the current state and at the same time the proposal of adjustments to the technology or parameters, the introduction of the wire into the drawing machine. The problem arises when the introduction of wire with a diameter of 14 mm from the material CK 67 to the drawbenches Schumag. If we introduce the wire into the drawing machines with two primary beams leads to a buckling of the wire and pack between the drawing die and the boot device. For the introduction of wire are used hydraulic boot collets, which are controlled semi-automatically. In connection with professional studies and on the basis of the calculation, simulation and practical experiment have been identified the conditions allowing the current method of deployment of wire to use.
Optimization of the Wire Drawing Process
Keywords: tažné zařízení; průvlak; simulace; experiment; Ansys; drawing device; drawing die; simulation; experiment; Ansys